John Grimes Walker papers - Walker, John Grimes, 1835-1907.
Letterbooks relating chiefly to Walker's service in the U.S. Navy and to family matters. Documents his service as secretary of the U.S. Light-House Board and commander in chief of the U.S. Navy Squadron of Evolution and his tours of duty in South America and Hawaii.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Walker family; United States. -- Light-House Board; United States. -- Navy -- Foreign service -- Hawaii; United States. -- Navy -- Foreign service -- South America; United States. -- Navy. -- Squadron of Evolution; Naval officers